DETERMINING THE RELATIONSHIP BETWEEN METAL CONTAMINATION AND PEROXIDE ACTIVITY IN GRASS CARP FROM INDUS RIVER (Journal of Medical & Health Sciences Review, 2025)
Heavy metals are important contaminants of aquatic system and can induce oxidative stress in fish. The aim of this research is to evaluate relationship between metals (Zn, Cu, Cr, Ni and Co) contamination and peroxidase activity in liver, gills, kidney heart and muscles in Ctenopharyngodon idella. Fish sample were collected from various sites of Indus River and brought to the laboratory for further study by preserving them in crushed dried ice. Water samples were also taken from the sampling sites to check physico-chemical parameters. Fish was dissected to get organs kidney, liver, gills, heart and muscles. For the enzyme assay organs were homogenized in phosphate buffer (PH 6.5 to 7). The extracted organs were digested on hot plate to determine the concentration of selected heavy metals by using atomic absorption spectrophotometer. Highly Significant difference was observed in peroxidase activity statistically at p< 0.05. The sequence of heavy metals found in riverine C. idella was Zn>Co>Cr>Ni>Cu, Zn>Ni>CuCo, Co>Zn>Cu>Ni>Cr, Zn>Cu>Co>Cr>Ni and Zn>Cu>Co>Cr>Ni for Liver>kidney>gills>heart>muscles, respectively. Metal concentration was observed lower in hatchery raised C. idella. This study could be potentially helpful in providing important information regarding how fish antioxidant systems are affected by the presence of heavy metals.